2021
DOI: 10.3390/cancers13205071
|View full text |Cite
|
Sign up to set email alerts
|

Value of Assessing Peripheral Vascularization with Micro-Flow Imaging, Resistive Index and Absent Hilum Sign as Predictor for Malignancy in Lymph Nodes in Head and Neck Squamous Cell Carcinoma

Abstract: Ultrasound-guided fine needle aspiration cytology (USgFNAC) is commonly used for nodal staging in head and neck squamous cell cancer (HNSCC). Peripheral vascularity is a described feature for node metastasis. Micro-flow imaging (MFI) is a new sensitive technique to evaluate micro-vascularization. Our goal is to assess the additional value of MFI to detect malignancy in lymph nodes. A total of 102 patients with HNSCC were included prospectively. USgFNAC was performed with the Philips eL18–4 transducer. Cytologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Other imaging modalities, such as Photoacoustic imaging, have been employed to visualize microvasculature structure [ 25 ]; though, it is only applicable for superficial tumors [ 26 ]. Recently, superb microvascular imaging (SMI) [ 27 ] and microflow imaging [ 28 ] modalities have been investigated for detecting metastatic ALN, without using a contrast agent; however, the diagnosis is mostly based on pixel counting and visual inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Other imaging modalities, such as Photoacoustic imaging, have been employed to visualize microvasculature structure [ 25 ]; though, it is only applicable for superficial tumors [ 26 ]. Recently, superb microvascular imaging (SMI) [ 27 ] and microflow imaging [ 28 ] modalities have been investigated for detecting metastatic ALN, without using a contrast agent; however, the diagnosis is mostly based on pixel counting and visual inspection.…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al previously showed that MFI can evaluate micro blood flow in detail, and it can be used to assess the vascular features contributing to the diagnosis of malignant breast masses; this association may be modified by age [ 30 ]. MFI has a high predictive value for cytological malignancies in neck metastases by assessing peripheral vascularization [ 10 ]. Conversely, Cappelli et al suggested that MFI shows tiny blood vessels in more detail [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…TRUS is an ultrasound technique that can distinguish between different layers of rectal wall infiltration, especially in early stage tumors [ 9 ]. A new advanced ultrasound modality, termed micro-flow imaging (MFI), is more sensitive and specific in detecting low blood flow signals within the lesion compared with color Doppler [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…MFI is a new high-resolution flow US imaging technique that discriminates Doppler signals from blood flow and tissue sources, thus enabling accurate evaluation of microvascular and low-velocity blood flow without the use of US contrast agents. [ 78 , 79 ] MFI can more accurately reflect the morphology of the blood vessels within the polyp and improve the ability to identify the nature of the polypoid lesion of the gallbladder, thus providing a US diagnostic basis for choosing the appropriate treatment for the patient. [ 80 ]…”
Section: Diagnosismentioning
confidence: 99%